MRI-LINAC beam profile measurements using a plastic scintillation dosimeter. (May 2020) - Madden, Levi; Archer, James; Li, Enbang; Jelen, Urszula; Dong, Bin; Holloway, Lois; Rosenfeld, Anatoly
Highlights: In-house plastic scintillation dosimeter and radiochromic film used to measure beam profiles. Measurements made on 1T in-line MRI-LINAC. Performance of PSD was comparable to other trusted detectors reported in the literature. Abstract: Plastic scintillation dosimeters (PSDs) possess many desirable qualities for dosimetry with LINACs. These qualities are expected to make PSDs effective for MRI-LINAC dosimetry, however little research has been conducted investigating their dosimetric performance with MRI-LINACs. In this work, an in-house PSD was used to measure 8 beam profiles with an in-line MRI-LINAC, compared with film measurements. One dimensional global gamma indices ( γ ) and corresponding γ pass rates were calculated to compare PSD and film profiles for the 1%/1 mm, 2%/2 mm and 3%/3 mm criterion. The mean global pass rates were 85.8%, 97.5% and 99.4% for the 1%/1 mm, 2%/2 mm and 3%/3 mm criteria, respectively. The majority of the γ failures occurred in the penumbral regions. Penumbra widths were measured to be slightly narrower with the PSD compared to film, however, the uncertainties in the measured penumbra widths brought the PSD and film penumbra widths into agreement. Differences in dose were calculated between the PSD and film, and remained within 2.2% global agreement for the central regions and 1.5% global agreement for out of field regions. These values for range of agreement were similar to the those reported in the literature for other dosimeters which are trusted for relative MRI-LINAC dosimetry.